Exploring the added value of hospital-registry data for showing local service outcomes: cancers of the ovary, fallopian tube and peritoneum. Issue 2 (3rd February 2019) - Roder, David; Davy, Margaret; Selva-Nayagam, Sid; Paramasivam, Sellvakumaran; Adams, Jacqui; Keefe, Dorothy; Miller, Caroline; Powell, Kate; Fusco, Kellie; Buranyi-Trevarton, Dianne; Oehler, Martin K
Abstract : Objectives: To explore the added value of hospital-registry data on invasive epithelial ovarian, tubal and peritoneal cancers. Design: Historic cohort analyses. Methods: Unadjusted and adjusted regression. Setting: Major South Australian hospitals. Participants: 1596 women (1984–2015 diagnoses). Results: 5-Year and 10-year survival was 48% and 41%, respectively, equivalent to relative survival for Australia and the USA. After adjusting for age, clinical and geographic factors, risk of ovarian cancer death was 25% lower in 2010–2015 than 1984–1989. Women generally had surgical treatment (87%) in their first round of care. This was more common for younger patients (adjusted OR (95% CIs) 0.17 (0.04 to 0.65) for 80+ vs <40 years) and earlier International Federation of Gynecology and Obstetrics stages (adjusted OR 0.48 (0.13 to 1.78) for stage IIIB/C and 0.13 (0.04 to 0.45) for stage IV vs stage IA). Most (74%) had systemic therapy, which was more common for advanced stages (adjusted ORs >15.0 for stages III and IV vs stage IA). Few (9%) had radiotherapy. Women generally had systemic therapy (74%), without difference by service accessibility and socioeconomic disadvantage, suggesting equity. However, surgery was less common for residents of the most compared with least remote areas (adjusted OR 0.49 (0.24 to 0.99)); and more common prior to adjustment in the highest versus lowest socioeconomic category (unadjusted OR 1.55 (1.01 to 2.39)), but this elevation did not apply after adjustment (adjusted OR 0.19 (0.63 to 2.25)), with the difference largely explained by stage. Conclusions: Hospital-registry data add value for assessing local service delivery. Equivalent survival to Australia-wide and USA survival, and temporal gains after adjusting for stage and other patient characteristics are reassuring. Survival gains may reflect therapeutic benefits of more extensive surgery and improved chemotherapy regimens.